Role of risk perceptions and vaccine hesitancy on decision-making among low-income mothers in Kenya: a qualitative study - Stephen Gichuhi Kimotho (BMJ Public Health)
Introduction Vaccine hesitancy among mothers in low-income communities in Kenya presents a serious obstacle to achieving successful childhood immunisation. The aim of this study was to explore the determinants of vaccine hesitancy among mothers from low-income rural communities, risk perceptions associated with vaccines and how these factors influence decision-making regarding their children’s immunisation.Methods A qualitative descriptive study was conducted in three counties in Kenya (Murang’a, Kiambu and Machakos) using in-depth interviews and focus group discussions with mothers of children under 5 years. Participants were purposively sampled from low-income rural communities and were mothers attending postnatal clinics at various health facilities. Thematic analysis was used to identify key themes and subthemes, coding of transcripts, identification of patterns and organisation of themes into categories.Results Several critical factors that contribute to vaccine hesitancy among mothers regarding their children’s immunisation were identified through thematic analysis. Safety concerns emerged as a primary issue, with mothers expressing fears of adverse reactions such as fever, pain, swelling or other unexpected complications. Misinformation significantly influenced perceptions, including beliefs that vaccines might cause infertility or long-term health problems. Distrust in the health system further exacerbated hesitancy, with mothers questioning the quality, administration and motives of vaccinators. Limited vaccine knowledge also played a role, which led to misconceptions about the severity and risks of vaccine-preventable diseases. Moreover, sociocultural and religious beliefs influenced decision-making, with some mothers viewing vaccines as unsafe or ineffective, driven by cultural norms, reliance on traditional remedies or religious objections.Conclusions This study provides valuable insights into the complexities of vaccine hesitancy among mothers in low-income communities in Kenya. Furthermore, the results emphasise the complex nature of hesitancy, driven by an interplay of safety concerns, misinformation, distrust, limited knowledge, and sociocultural and religious influences. Addressing these determinants requires interventions that would prioritise clear and accurate communication about vaccine safety, engagement with community and religious leaders, and strengthening trust in healthcare providers and systems. Additionally, enhancing vaccine knowledge through targeted health education programmes would be crucial for empowering mothers to make informed decisions about their children’s health.